Etymological dictionary of the Hittite inherited lexicon - Kloekhorst, Alwin (Leiden Indo-European etymological dictionary series, 2008)
"Hittite is the oldest attested Indo-European language and therefore of paramount importance for comparative Indo-European linguistics. Although in the last few decades our knowledge of the synchronic and historical linguistics of Hittite has profoundly increased, these new insights have not been systematically applied to the whole Hittite material. This book fills this gap by, for the first time, providing an etymological dictionary of the entire Hittite lexicon of Indo-European origin in which all words are treated in a coherent way. Furthermore, it provides a thorough description of the synchronic phonological system of Hittite as well as a comprehensive study of the Hittite historical morphology and phonology. The result is a monumental handbook that will form an indispensable tool for Indo-Europeanists and Hittitologists alike."--Jacket